The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.05.04.039719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative meta andin silicoanalysis of differentially expressed genes and proteins in canine and human bladder cancer

Abstract: 17Running Title 2 This is a provisional file, not the final typeset article analysis involving canine and human transcriptome data provided several genes with potential to be 36 markers for both human and canine bladder tumors and these genes should be considered for future 37 studies on canine bladder cancer. 38 39

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Canine UC is known for its increased invasiveness at the time of diagnosis and is an important model for muscle-invasive diseases in humans ( 1 , 4 ). However, despite the difficulties associated with the treatment of this tumor type in dogs, most studies related to biomarkers for bladder UC in veterinary medicine analyze isolated molecules without assessing their prognostic value or association with other variables ( 7 ). For this reason, we investigated the expression of Caveolin-1 and GATA-3 in canine UC to assess their expression patterns and associate them with clinicopathological findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Canine UC is known for its increased invasiveness at the time of diagnosis and is an important model for muscle-invasive diseases in humans ( 1 , 4 ). However, despite the difficulties associated with the treatment of this tumor type in dogs, most studies related to biomarkers for bladder UC in veterinary medicine analyze isolated molecules without assessing their prognostic value or association with other variables ( 7 ). For this reason, we investigated the expression of Caveolin-1 and GATA-3 in canine UC to assess their expression patterns and associate them with clinicopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Gambim et al ( 7 ) performed a meta-analysis of literature on biomarkers for canine UC and demonstrated a lack of markers for this tumor subtype. Previous studies that investigated biomarkers have usually described the marker expression pattern with no association with clinical and pathological factors ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urothelial carcinomas (UC) are the most common genitourinary tumors in dogs and closely mimic the muscle-invasive phenotype that is seen in humans [ 33 , 36 , 161 ] ( Figure 6 ). The BRAF V595E mutation is seen in roughly 85% of canine patients with UC, which has prompted recent investigation into the efficacy of vemurafenib in dogs [ 162 , 163 , 164 , 165 , 166 ]. Several groups have documented the immune landscape and mRNA expression of canine UC, revealing its utility as a relevant translational model [ 37 , 38 , 167 , 168 , 169 ].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%